Synthesis of new graphene oxide/TiO2 and TiO2/SiO2 nanocomposites and their evaluation as photocatalysts - Rosenthal, Marta; Biktagirov, Timur; Schmidt, Wolf Gero; Wilhelm, René (Catalysis Science & Technology)
Composites of different graphene oxide types, TiO 2 materials, and especially synthetic routes influence the photocatalytic activity of the resulting material.

Adsorption of Cyclic (Alkyl) (Amino) Carbenes on Monohydride Si(001) Surfaces: Interface Bonding and Electronic Properties - Meier, Lukas; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, Andrey N.; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina
Dataset of the publication "Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field" H. Rose, A. N. Vasil’ev, O. V. Tikhonova, T. Meier, and P. R. Sharapova, Phys. Rev. A 107, 013703 (2023). ( https://doi.org/10.1103/PhysRevA.107.013703 ). The zip file includes the data on which the plots shown in figures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, and 11 are based.

Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations - Trautmann, Alexander; Stein, Markus; Schäfer, Felix; Anders, Daniel; Ngo, Cong; Steiner, Johannes Tilmann; Reichelt, Matthias; Chatterjee, Sangam; Meier, Torsten
Dataset of the publication “Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations”, A. Trautmann, M. Stein, F. Schäfer, D. Anders, C. Ngo, J. T. Steiner, M. Reichelt, S. Chatterjee, and T. Meier, Proc. SPIE 12419, Ultrafast Phenomena and Nanophotonics XXVII, 124190A (2023) ( https://doi.org/10.1117/12.2650169 ). The zip file includes the data on which the plots are based.

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng
Dataset of the publication “Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse”, by X. Song, S. Yang, G. Wang, J. Lin, L. Wang, T. Meier, and W. Yang, published in Optics Express 31, 18862 (2023) , https://doi.org/10.1364/OE.491418 . The zip file includes a brief description, the data on which the plot of figures 1 – 3 are based, and matlab figure files.

Excitonic anomalous currents in semiconductor quantum wells - Ngo, Cong; Priyadarshi, Shekhar; Duc, Huynh Thanh; Bieler, Mark; Meier, Torsten
Dataset of the publication “Excitonic anomalous currents in semiconductor quantum wells”, by C. Ngo, S. Priyadarshi, H. T. Duc, M. Bieler, and T. Meier, published in Physical Review B 108, 165302 (2023) ( https://doi.org/10.1103/PhysRevB.108.165302 ) The zip file includes a brief description and the data on which the plots of figures 2 – 10 are based, and the codes used for the numerical evaluations (k.p and semiconductor Bloch equations).

Terahertz-induced anomalous currents following the optical excitation of excitons in semiconductor quantum wells - Ngo, C.; Priyadarshi, S; Duc, H. T.; Meier, Torsten
Dataset of the publication “Terahertz-induced anomalous currents following the optical excitation of excitons in semiconductor quantum wells“, C. Ngo, S. Priyadarshi, H. T. Duc, M. Bieler, and T. Meier, Proc. SPIE 12419, Ultrafast Phenomena and Nanophotonics XXVII, 124190G (2023) ( https://doi.org/10.1117/12.2646022 ). The zip file includes the data on which the plots are based.

Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation - Zuo, Ruixin; Song, Xiaohong; Ben, Shuai; Meier, Torsten; Yang, Weifeng
Dataset of the publication “Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation“, by Ruixin Zuo, Xiaohong Song, Shuai Ben, Torsten Meier, and Weifeng Yang, published in PHYSICAL REVIEW RESEARCH 5, L022040 (2023) ( https://doi.org/10.1103/PhysRevResearch.5.L022040 ) The zip file includes the data on which the plots 2 – 9 are based.

Microscopic simulations of high harmonic generation from semiconductors - Trautmann, Alexander; Al., Et
Dataset of the publication “Microscopic simulations of high harmonic generation from semiconductors” by A. Trautmann, R. Zuo, G. Wang, W.-R. Hannes, S. Yang, L. H. Thong, C. Ngo, J. T. Steiner, M. Ciappina, M. Reichelt, H. T. Duc, X. Song, W. Yang, and T. Meier, Proc. SPIE 11999, Ultrafast Phenomena and Nanophotonics XXVI, 1199909 (2022) ( https://doi.org/10.1117/12.2607447 ). The zip file includes the data on which the plots are based.

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, Stefan; Trifonov, Artur V.; Reichhardt, Rilana; Reichelt, Matthias; Bayer, Manfred; Akimov, Ilya A.; Meier, Torsten
Dataset of the publication "Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light" H. Rose, S. Grisard, A. V. Trifonov, R. Reichhardt, M. Reichelt, M. Bayer, I. A. Akimov, and T. Meier, Proc. SPIE 12419, Ultrafast Phenomena and Nanophotonics XXVII, 124190H (2023). ( https://doi.org/10.1117/12.2647700 ). The zip file includes the data on which the plots shown in figures 1 and 2 are based.

Microscopic simulations of high harmonic generation from semiconductors - Trautmann, Alexander; Zuo, Ruixin; Wang, G.; Hannes, W.-R.; Yang, S.; Thong, L. H.; Ngo, Cong; Steiner, Johannes; Ciappina, M.; Reichelt, Matthias; Thanh Huynh, Duc; Song, Xiaohong; et al.
Dataset of the publication “Microscopic simulations of high harmonic generation from semiconductors” by A. Trautmann, R. Zuo, G. Wang, W.-R. Hannes, S. Yang, L. H. Thong, C. Ngo, J. T. Steiner, M. Ciappina, M. Reichelt, H. T. Duc, X. Song, W. Yang, and T. Meier, Proc. SPIE 11999, Ultrafast Phenomena and Nanophotonics XXVI, 1199909 (2022) ( https://doi.org/10.1117/12.2607447 ). The zip file includes the data on which the plots are based.

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Ali, Usman; Holthaus, Martin; Meier, Torsten

Temporal Sorting of Optical Multiwave-Mixing Processes in Semiconductor Quantum Dots - Grisard, Stefan; Trifonov, Artur V.; Rose, Hendrik; Reichhardt, Rilana; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (ACS Photonics)

Circularly polarized electroluminescence from a single-crystal organic microcavity light-emitting diode based on photonic spin-orbit interactions - Jia, Jichao; Cao, Xue; Ma, Xuekai; De, Jianbo; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Experimental studies of the excitonic nonlinear response of GaAs-based type-I and type-II quantum well structures interacting with optical and terahertz fields - Meier, Torsten; Stein, M.; Schäfer, F.; Anders, D.; Littmann, J. H.; Fey, M.; Trautmann, Alexander; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Fuchs, C.; Volz, K.; et al. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons is investigated experimentally using polarization resolved four wave mixing, optical-pump optical-probe, and optical-pump Terahertz-probe spectroscopy. The four-wave mixing data reveal clear signatures of coherent biexcitons which concur with straight-forward polarization selection rules at the Γ point. The type-I samples show the well-established time-domain beating signatures in the transients as well as the corresponding spectral signatures clearly. The latter are also present in type-II samples; however, the smaller exciton and biexciton binding energies in these structures infer longer beating times which, in turn, are accompanied by faster dephasing of the type-II exciton coherences. Furthermore, the THz absorption following spectrally narrow, picosecond excitation at energies in the vicinity of the 1s exciton resonance are discussed. Here, the optical signatures yield the well-established redshifts and blueshifts for the appropriate polarization geometries in type-I quantum well samples also termed “AC Stark Effect”. The THz probe reveals intriguing spectral features which can be ascribed to coherent negative absorption following an excitation into a virtual state for an excitation below the 1s exciton resonance. Furthermore, the scattering and ionization of excitons is discussed for several excitation geometries yielding control rules for elastic and inelastic quasiparticle collisions.

Terahertz-induced anomalous currents following the optical excitation of excitons in semiconductor quantum wells - Meier, Torsten; Ngo, C.; Priyadarshi, S.; Duc, H. T.; Bieler, M. (Ultrafast Phenomena and Nanophotonics XXVII)
Anomalous currents refer to electronic currents that flow perpendicularly to the direction of the accelerating electric field. Such anomalous currents can be generated when Terahertz fields are applied after an optical interband excitation of GaAs quantum wells. The underlying processes are investigated by numerical solutions of the semiconductor Bloch equations in the length gauge. Excitonic effects are included by treating the manybody Coulomb interaction in time-dependent Hartree-Fock approximation and additionally also carrier-phonon scattering processes are considered. The band structure and matrix elements are obtained from a 14-band k · p model within the envelope function approximation. The random phase factors of the matrix elements that appear due to the separate numerical diagonalization at each k-point are treated by applying a smooth gauge transformation. We present the macroscopic Berry curvature and anomalous current transients with and without excitonic effects. It is demonstrated that the resonant optical excitation of excitonic resonances can significantly enhance the Berry curvature and the anomalous currents.

Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations - Meier, Torsten; Trautmann, Alexander; Stein, M.; Schäfer, F.; Anders, D.; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Chatterjee, S. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons excited by optical fields is analyzed by numerical solutions of the semiconductor Bloch equations. Differential absorption spectra are computed for resonant pumping at the exciton resonance and the dependence of the absorption changes on the polarization directions of the pump and probe pulses is investigated. Coherent biexcitonic many-body correlations are included in our approach up to third-order in the optical fields. Results are presented for spatially-direct type-I and spatiallyindirect type-II quantum well systems. Due to the spatial inhomogeneity, in type-II structures a finite coupling between excitons of opposite spins exists already on the Hartree-Fock level and contributes to the absorption changes for the case of opposite circularly polarized pump and probe pulses.

Gain recovery dynamics in active type-II semiconductor heterostructures - Meier, Torsten; Schäfer, F.; Stein, M.; Lorenz, J.; Dobener, F.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Stolz, W.; Volz, K.; Hader, J.; Moloney, J.V.; et al. (Applied Physics Letters)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)